Metatrichia vesparium - Krivomaz, Т. І.; Michaud, A.; Minter, D. W. (CABI, 2012)
Diagnostic features. The clustered sporangia with a distinctive shape and papery texture resembling miniature wasp nests, the shining purple-red sporangia, and the red spore mass all make this an easy species to identify. When stalks are joined this species can look like M. floriformis (Schwein.) Nann.-Bremek., but the spore mass colour is usually sufficient to separate them and, if there is any doubt, the spiny capillitium of M. vesparium is diagnostic.
Keywords: myxomycetes; міксоміцети; Metatrichia vesparium